Toward Evidence Based Practice. Issue 5 (September 2015) - Lewis, Judith A.; Krowchuk, Heidi VonKross; Woodgate, Roberta
<x xml:space="preserve">Abstract</x> Experts suggest how 6 research articles can be used in nursing practice.